2021
DOI: 10.1111/bjh.17608
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response rate and predictors of response to BNT162b2 mRNA COVID19 vaccine in patients with multiple myeloma

Abstract: Multiple myeloma (MM) patients are at excess risk for clinically significant COVID19 infection. BNT162b2 mRNA COVID19 (BNT162b2) vaccine provides effective protection against COVID19 for the general population, yet its effect in MM patients may be compromised due to disease and therapy-related factors and was not yet evaluated. This single-centre prospective study included MM patients tested for serological response 14-21 days post second vaccine. Vaccinated healthy volunteers served as controls. In all, 171 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
103
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(126 citation statements)
references
References 23 publications
19
103
2
2
Order By: Relevance
“…We reviewed the literature to gather information on the seroconversion rates after receiving a COVID-19 vaccine in patients with hematologic malignancies. We selected 18 series that provided anti-SARS-CoV-2 spike protein IgG seroconversion rates after full COVID-19 vaccination detailed by hematologic malignancy diagnosis, with at least 20 patients per group (Figure 1 and Supplemental Table 1) (2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The literature review also included six additional series that are not included in Figure 1, three due to sampling of serum antibodies before achieving full vaccination as evidenced by lower seroconversions in the healthy control group compared to the rest of the series (20,21), and three that did not provide breakdown of the data according to different histological diagnoses (22,23).…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…We reviewed the literature to gather information on the seroconversion rates after receiving a COVID-19 vaccine in patients with hematologic malignancies. We selected 18 series that provided anti-SARS-CoV-2 spike protein IgG seroconversion rates after full COVID-19 vaccination detailed by hematologic malignancy diagnosis, with at least 20 patients per group (Figure 1 and Supplemental Table 1) (2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The literature review also included six additional series that are not included in Figure 1, three due to sampling of serum antibodies before achieving full vaccination as evidenced by lower seroconversions in the healthy control group compared to the rest of the series (20,21), and three that did not provide breakdown of the data according to different histological diagnoses (22,23).…”
Section: Main Textmentioning
confidence: 99%
“…Important variables related to the hematologic malignancy, including being on active therapy, the type of therapy, being on watchful waiting before therapy, or having completed therapy, varied among the series and diagnoses. As a comparison, we provide the rates of seroconversion of healthy subjects from the series that included concomitant testing, which in some cases were age-matched controls (4,6,10,12,13,15,17,19,24). The combined healthy subjects group adds to 729 individuals, with seroconversion rates between 98-100% (Figure 1 and Supplemental Table 1), suggesting that these series adequately tested for anti-SARS-CoV-2 spike protein seroconversion at the time that healthy subjects would have responded to the vaccine.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary data on serological responses in onco-hematological patients with mRNA SARS-CoV-2 vaccines confirmed lower response rates in hematological patients compared to the general population [ 14 , 15 , 19 ]. However, the reported seroconversion rates (39.5% in CLL patients [ 17 ], 75% in general hematological patients [ 15 ], 76% in active MM patients [ 20 ] and 78% in allo-SCT recipients [ 16 ] are really encouraging and seem higher than previously reported data with other vaccines in these immunocompromised patients. These preliminary data support the higher immunogenicity of mRNA vaccines compared to traditional vaccine compounds.…”
Section: Methodsmentioning
confidence: 96%
“…A recent study with mRNA SARS-CoV-2 vaccines in MM patients showed good serological response rates (76% of patients with active MM patients vs 100% in Smoldering MM patients). Multivariate analysis revealed a negative impact on serological responses of older age, exposure to ≥4 novel anti-myeloma drugs and the presence of severe hypogammaglobulinemia, whereas none of the novel agents individually decreased the response rate [ 20 ]. Altogether, these data suggest that MM patients should be considered a priority in vaccination programs: Timing of vaccination.…”
Section: Methodsmentioning
confidence: 99%